2017
DOI: 10.3390/nu9050507
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Arginine Administration Promotes Proangiogenic Cells Mobilization and Attenuates Lung Injury in Mice with Polymicrobial Sepsis

Abstract: This study investigated the influence of intravenous arginine (Arg) administration on alteration of circulating proangiogenic cells and remote lung injury in a model of polymicrobial sepsis. Mice were assigned to one normal control group (NC) and two sepsis groups that were induced by cecal ligation and puncture (CLP). One of the sepsis groups was injected with saline (SS), whereas the other (SA) was administered with a single bolus of 300 mg Arg/kg body weight via the tail vein 1 h after CLP. Septic mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Mice were randomly assigned to a normal control (NC) group (n = 6), a sham group (n = 6), a septic saline (SS, n = 24) group, and a septic Arg (SA, n = 24) group. Polymicrobial peritonitis sepsis was induced by cecal ligation and puncture (CLP) as described previously [17]. Mice were anesthetized, a midline incision (1~1.5 cm) was made in the abdominal wall, and the cecum was identified.…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were randomly assigned to a normal control (NC) group (n = 6), a sham group (n = 6), a septic saline (SS, n = 24) group, and a septic Arg (SA, n = 24) group. Polymicrobial peritonitis sepsis was induced by cecal ligation and puncture (CLP) as described previously [17]. Mice were anesthetized, a midline incision (1~1.5 cm) was made in the abdominal wall, and the cecum was identified.…”
Section: Study Protocolmentioning
confidence: 99%
“…Also, Arg enhanced the immune response and protein turnover and showed beneficial effects in a porcine model of endotoxemia [16]. A study performed by our laboratory showed that intravenous Arg administration attenuated sepsis-induced lung injury [17]. Since NO is an inhibitor of caspase-1 [18], availability of NO may inhibit NLRP3 inflammasome activation and subsequent IL-1β and IL-18 production.…”
Section: Introductionmentioning
confidence: 99%
“…Despite enormous advances in treating lung injuries, therapeutic options with high efficacy and less side effect are imperative, considering its high morbidity and mortality all over the world [18]. Amino acids, such as glutamine, arginine, and glycine, have attracted more and more attention due to various bioactivities, such as anti-inflammatory and anti-oxidative effects, in the lung and other tissues [19][20][21][22]. Our recent study has showed that glycine pretreatment effectively alleviated LPS-induced lung injury by inhibiting the inflammation and apoptosis of alveolar cells [23].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, the effect of sepsis on the number of EPCs in patients peripheral blood had been different. In 2007, Mayr et al found that the number of EPCs in healthy volunteers decreased signi cantly after infusion of 2ng/Kg lipopolysaccharide (LPS) [17],while recent studies have shown that the number of EPCs in patients with severe sepsis was signi cantly elevated and negatively correlated with mortality [18][19][20]. Patschan et al found that the numbers of CFU-ECs (colony-forming unit endothelial cells) was lower in patients with sepsis than in healthy controls [21].…”
Section: Introductionmentioning
confidence: 99%